1996
DOI: 10.1007/bf00014688
|View full text |Cite
|
Sign up to set email alerts
|

Some allometric and non-allometric relationships between chlorophyll-a and abundance variables of phytoplankton

Abstract: We analysed data from three Bulgarian reservoirs, with trophic status from meso to eutrophic . Two kinds of relations (non-allometric and allometric) of chlorophyll with phytoplankton density, biovolume and surface area were investigated . The non-allometric relationships compare these phytoplankton variables with chlorophyll-a concentration, while the allometric ones include comparisons of average individual volume (AIV) of phytoplankters with chlorophyll-a content per individual (Chl .N -1 ), per unit biovol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
4

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 18 publications
0
11
0
4
Order By: Relevance
“…One possible hypothesis to explain the relatively low chlorophyll yield per unit phosphorus is that the chlorophyll per unit biomass of algal cells is less in nearshore coastal waters than in lakes of Florida. The use of chlorophyll as an indicator of algal biomass can be problematic, however, because the ratio of chlorophyll to biomass or biovolume varies among species, systems, and environmental conditions (Heyman and Lundgren 1988;White et al 1988;Kalchev et al 1996). Nevertheless, if the chlorophyll to biomass ratio in nearshore coastal waters of Florida is significantly less than the chlorophyll to biomass ratio in freshwater lakes, this may explain the low yields of chlorophyll per unit of phosphorus in nearshore coastal waters (Fig.…”
Section: Fig 2 Relations Between Total Phosphorus and Chlorophyll Fmentioning
confidence: 95%
“…One possible hypothesis to explain the relatively low chlorophyll yield per unit phosphorus is that the chlorophyll per unit biomass of algal cells is less in nearshore coastal waters than in lakes of Florida. The use of chlorophyll as an indicator of algal biomass can be problematic, however, because the ratio of chlorophyll to biomass or biovolume varies among species, systems, and environmental conditions (Heyman and Lundgren 1988;White et al 1988;Kalchev et al 1996). Nevertheless, if the chlorophyll to biomass ratio in nearshore coastal waters of Florida is significantly less than the chlorophyll to biomass ratio in freshwater lakes, this may explain the low yields of chlorophyll per unit of phosphorus in nearshore coastal waters (Fig.…”
Section: Fig 2 Relations Between Total Phosphorus and Chlorophyll Fmentioning
confidence: 95%
“…The linear relationship between chlorophyll and phytoplankton biovolume has been widely studied (Tolstoy 1979;Desortová 1981;Vörös and Padisák 1991;Jones et al 1996;Kalchev et al 1996), while allometric relationships have also been found between them by (Vörös and Padisák 1991). The light attenuated by phytoplankton in a water column depends on phytoplankton biomass and the extinction of light per unit biomass: extinction coefficient (EC) (Caraco et al 1997).…”
Section: Model Assumptionsmentioning
confidence: 98%
“…Accordingly, estimation of algal biomass is very crucial. Chlorophyll concentration was widely used as a common predictor's technique for monitoring the reliability picture of dissolved nutrients and algal biomass in aquatic habitats (Fogg 1975, Tolstoy 1979, Desortová 1981, Vörös and Padisák 1991and Kalchev et al 1996and Halil et al 2008. Chlorophyll a is the main photosynthetic pigment in all oxygen-evolving photosynthetic algae while other algal pigments have limited distribution and considered as accessory or secondary pigments (Akpan 1994).…”
Section: Introductionmentioning
confidence: 99%